S’ajuster « par le corps » au patient-enfant : une approche micrologique de l’activité d’enquête du psychomotricien - Marion Paggetti (Questions Vives)
This contribution aims to participate in the analysis of body-dominant interactions conducted in activities addressed to others by relying on an understanding of the adjustments made by psychomotor therapists working with children. The theoretical framework of J. Dewey's theory of inquiry is used as a model of intelligibility of the process by which professionals adjust or readjust their therapeutic actions and invites to focus the attention on the micro-perturbations that the psychomotrician encounters in the course of his activity. The micro-adjustments are documented and highlight the conduct of a singular form of inquiry whose putting into words by the practitioners participates in the definition of the professional genre.